2008
DOI: 10.2217/17455111.2.3.289
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Among Youth from Eight African Countries and Associations with Adverse Health Behaviors

Abstract: Bullying is a form of youth aggression associated with more serious violent behaviors and with an increased likelihood of physical and psychosomatic health problems. Studies describing the burden of bullying and relationships with adverse health behaviors among youth in Africa are lacking. Using data from the Global School-based Student Health Survey, we estimated the prevalence of exposure to bullying among youth from Kenya,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 12 publications
9
74
4
Order By: Relevance
“…Data from Kenya, Namibia, Swaziland, Tanzania, Zimbabwe and five other African countries [54] have shown that among youth, the risk of bullying increased if they indulged in health compromising behaviors. Similarly, Fleming and Jacobsen [33] found that tobacco use, alcohol use, drug use and engaging in sexual intercourse were associated with the probability of being bullied among adolescents in several LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Kenya, Namibia, Swaziland, Tanzania, Zimbabwe and five other African countries [54] have shown that among youth, the risk of bullying increased if they indulged in health compromising behaviors. Similarly, Fleming and Jacobsen [33] found that tobacco use, alcohol use, drug use and engaging in sexual intercourse were associated with the probability of being bullied among adolescents in several LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few African countries that have school-based data on bullying [15][16][17][18][19][20][21][22], some context specific phenomena have emerged that have not been observed or widely studied elsewhere: HIV-status related bullying and an inverse relationship with having siblings [23]. These preliminary findings unique to African countries highlight the need for continued research on bullying patterns across the continent.…”
Section: Introductionmentioning
confidence: 98%
“…Despite a growing body of cross-sectional research on the link between drug use and bullying behaviour during school years (Brown, Riley, Butchart, & Kann, 2008;Moon & Alarid, 2014;Niemelä et al, 2011), no previous meta-analysis has been conducted to systematically synthesize relevant evidence and to identify the magnitude and the direction of this association. The current paper addresses this gap by meta-analysing results from existing published and unpublished studies following a comprehensive systematic review.…”
Section: Introductionmentioning
confidence: 99%